Corporate Liability Of Banks For Failures In Implementing Green Banking Principles: Tanggung Jawab Korporasi Bank atas Kegagalan dalam Menerapkan Prinsip-Prinsip Perbankan Hijau - Romadoni, Rahayu Mulia; Mardiyati, Nursanti; Putri, Aisyah Nikita Permata (Perspektif Hukum, 2026)
The global transition toward a low-carbon economy is driving the adoption of Green Central Banking to integrate environmental risks into financial stability. In Indonesia, the Sustainable Finance mandate requires banks to implement ESG (Environmental, Social, and Governance) principles; however, lending practices to “brown sectors” remain prevalent. This normative legal research analyzes the standing of these principles and maps the legal liability of banks through statutory and conceptual approaches. The results indicate that these principles have transformed from soft law into hard law through OJK (Financial Services Authority) regulations. Non-compliance gives rise to multidimensional liability: administrative via OJK sanctions; civil through the Lender Liability doctrine (Article 1365 of the Indonesian Civil Code) for negligence in due diligence; and criminal regarding involvement in environmental degradation and money laundering risks. The study concludes that current liability mechanisms remain fragmented. Harmonization of regulations and the tightening of environmental legal audit standards in credit distribution are essential to mitigate legal risks and ensure banking compliance with national sustainability targets. The novelty of this research lies in its construction of a unified, multidimensional liability framework—integrating administrative, civil, and criminal law dimensions—specifically within the Indonesian legal context, an analytical synthesis that existing sustainable finance literature in Indonesia has not yet comprehensively addressed. Unlike prior studies that examine OJK regulations or the Lender Liability doctrine in isolation, this research maps the normative intersections between the Banking Law, UU PPLH, and POJK 51/2017 to expose systemic gaps and propose concrete directions for legal harmonization.